1996
DOI: 10.1073/pnas.93.15.7470
|View full text |Cite
|
Sign up to set email alerts
|

An interspecies hybrid RNA virus is significantly more virulent than either parental virus.

Abstract: Cucumber mosaic cucumovirus (CMV) infects a very wide range of plant species (>1000 species). We recently demonstrated that a previously undescribed gene (2b) encoded by RNA 2 of the tripartite RNA genome of CMV is required for systemic virus spread and disease induction in its hosts. Herein we report that when this CMV gene is replaced by its homologue from tomato aspermy cucumovirus (TAV), the resultant hybrid virus is significantly more virulent, induces earlier onset of systemic symptoms, and accumulates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(78 citation statements)
references
References 33 publications
5
71
0
2
Order By: Relevance
“…N-terminal region of 1a protein contains putative methyltransferase domain [39] and C-terminal region shows sequence similarity to viral helicases [16]. RNA 2 encodes for another protein 2b, which is expressed from the subgenomic RNA 4A and acts as suppressor of gene silencing [4,5,27]; plays a role in long distance movement of the virus [9,23,43,54] and also behave as pathogenicity determinant [10,41,43]. A recent finding suggested that this suppressor protein is indirectly involved in aphid transmission [56].…”
Section: Introductionmentioning
confidence: 99%
“…N-terminal region of 1a protein contains putative methyltransferase domain [39] and C-terminal region shows sequence similarity to viral helicases [16]. RNA 2 encodes for another protein 2b, which is expressed from the subgenomic RNA 4A and acts as suppressor of gene silencing [4,5,27]; plays a role in long distance movement of the virus [9,23,43,54] and also behave as pathogenicity determinant [10,41,43]. A recent finding suggested that this suppressor protein is indirectly involved in aphid transmission [56].…”
Section: Introductionmentioning
confidence: 99%
“…A subgenomic messenger corresponding to ORF 2b (RNA 4A) has been identified in infected plants and this RNA is translated in vitro into the expected 22 kDa protein (Xin et al, 1998). The genome of cucumoviruses contains a 2b gene at a position similar to that of the ilarvirus 2b gene (Ding et al, 1996). However, the ilarvirus 2b gene is almost twice as large as the cucumovirus 2b gene and there is no sequence similarity between the two types of gene whereas there is significant similarity between the four ilarvirus 2b genes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ilarvirus 2b gene is almost twice as large as the cucumovirus 2b gene and there is no sequence similarity between the two types of gene whereas there is significant similarity between the four ilarvirus 2b genes. The cucumoviral 2b gene plays a role in systemic spread of the virus and virulence determination, possibly by suppressing a host RNA silencing mechanism (Ding et al, 1996 ;Brigneti et al, 1998). A possible role of the 2b gene in ilarvirus replication has not yet been analysed.…”
Section: Introductionmentioning
confidence: 99%
“…1 The 2b protein is a determinant of virus symptoms and movement, and consequently plays an important part in the virulence of CMV. 2,3 For example, by transferring the 2b gene of a severe cucumovirus into a mild one, the symptoms induced by the mild strain were significantly enhanced. 3 The 2b protein is also a suppressor of two key plant antiviral defense systems: salicylic acid-mediated resistance, 4 and RNA silencing.…”
Section: The 2b Counter-defense Protein Of Cucumber Mosaic Virusmentioning
confidence: 99%